2007
DOI: 10.2353/ajpath.2007.060437
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Repulsive Guidance Molecule C during Inflammation Is Independent of Hfe and Involves Tumor Necrosis Factor-α

Abstract: Genetic iron overload, or hemochromatosis, can be caused by mutations in HFE, hemojuvelin, and hepcidin genes. Hepcidin, a negative regulator of intestinal iron absorption, is found to be inappropriately low in both patients and in animal models, indicating that proper control of basal hepcidin levels requires both hemojuvelin and HFE. In mice, repulsive guidance molecule c (Rgmc, the hemojuvelin mouse ortholog) and hepcidin levels are transcriptionally regulated during inflammation. Here, we report that basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
5
22
0
Order By: Relevance
“…Alternatively, proinflammatory mediators, released in response to LPS in one eye, may travel to the contralateral eye via circulation and elicit their effects. It has been shown that LPS may produce its effects on hepcidin expression in the liver through IL-6 and/or TNF-α in an autocrine manner [35]. Such intermediates may also be released into circulation from the retina of the LPS-injected eye and subsequently elicit their effects on hepcidin expression in the contralateral eye.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, proinflammatory mediators, released in response to LPS in one eye, may travel to the contralateral eye via circulation and elicit their effects. It has been shown that LPS may produce its effects on hepcidin expression in the liver through IL-6 and/or TNF-α in an autocrine manner [35]. Such intermediates may also be released into circulation from the retina of the LPS-injected eye and subsequently elicit their effects on hepcidin expression in the contralateral eye.…”
Section: Discussionmentioning
confidence: 99%
“…The first-strand cDNA synthesized (20 ml) was diluted to 120 ml with RNase-free water, 5 ml of which was used as a template in quantitative RT-PCRs. Adult human liver total RNA was purchased from Clontech Laboratories, Inc. Quantification of gene expression was performed by a Rotor Gene 3000 Real-time DNA Detection System (Montreal Biotech, Kirkland, QC, Canada) with QuantiTect SYBRGreen I PCR kits (Qiagen), as described previously (Constante et al 2007). The oligonucleotides used to amplify b-actin, HAMP, GATA-2, GATA-3, GATA-4, GATA-6, FOG-1, and FOG-2 genes are listed in Table 1.…”
Section: Cell Culturementioning
confidence: 99%
“…10 Most of the murine models display a mild anemia and hypoferremia after injection of inflammatory stimuli, but the hypoferremia normalizes within 24 to 72 hours. 18 Here, we report a rat model in which arthritis was induced on intraperitoneal administration of peptidoglycan-polysaccharidefragments (PG-APS). Arthritic rats develop a long-lasting anemia 19 with the features of ACD.…”
Section: Introductionmentioning
confidence: 99%
“…10 Most of the murine models display a mild anemia and hypoferremia after injection of inflammatory stimuli, but the hypoferremia normalizes within 24 to 72 hours. 18 Submitted December 19, 2008; accepted March 3, 2009. Prepublished online as Blood First Edition paper, March 17, 2009; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%